Gastro-Resistant Microparticles Produced by Spray-Drying as Controlled Release Systems for Liposoluble Vitamins - Francesca Terracina; Roberto Caruana; Francesco Paolo Bonomo; Francesco Montalbano; Mariano Licciardi (MDPI AG, 2022)
In the present study, gastro-resistant microparticles (MPs) were produced using the spray-drying technique as controlled-release systems for some model liposoluble vitamins, including retinyl-palmitate, retinyl-acetate, β-carotene, cholecalciferol and α-tocopherol. The gastroprotective action of three different gastro-resistant excipients, the anionic methacrylic copolymer (Eudraguard®® Biotic, E1207), the cellulose acetate phthalate (CAP) and whey proteins (WPs), was compared. The latter was used to produce a novel delivery system manufactured with only food-derived components, such as milk, and showed several improvements over the two synthetic gastro-resistant agents. Scanning electron microscopy (SEM) images showed a quite homogeneous spherical shape of all microparticle batches, with an average diameter between 7 and 15 μm. FTIR analysis was used to evaluate the effective incorporation of vitamins within the microparticles and the absence of any degradation to the components of the formulation. The comparison graphs of differential scanning calorimetry (DSC) confirmed that the spray drying technique generates a solid in which the physical interactions between the excipients and the vitamins are very strong. Release studies showed a prominent pH-controlled release and partially a delayed-release profile. Ex vivo permeation studies of retinyl palmitate, retinyl acetate and α-tocopherol revealed greater transmucosal permeation capacity for microparticles produced with the WPs and milk.